SOSIALISASI PEMANFAATAN HASIL HUTAN BUKAN KAYU (HHBK) SEBAGAI SUMBER ENERGI ALTERNATIF - Herman Siruru; Lieke Tan; Jimmy Titarsole; Leonard Dantje Liliefna; Rohny Setiawan Maail; Jimmy Johanson Fransz; Lydia Riekie Parera; Sofia Mustamu; Irwanto Irwanto; Billy Gilbert Anthonius; Sintia Cornelia Br Gurusinga; Setiani Br Ginting (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The energy needs of the world including Indonesia continue to increase every year. The most commonly used type of energy sources was dominated by fossil. Fossil energy sources were not environmentally friendly and were predicted to run out in a short period of time. Therefore, the alternative energy sources are needed, such as biomass or better known as bioenergy. The purpose of community service activities in Waai Village, Central Maluku Regency was to increase the community’s knowledge in utilizing biomass as an alternative energy source. The management of agroforestry in Waai village potentially produces many types of non-timber forest products (NTFPs) such as sago (Metroxylon sp.) which has husk as its waste after sago flour had been harvested for food. The implementation of the activity was held from July to August 2023, with activity phases including: social approach to the village government and AM GPM management and continued with visiting the community on Friday 11 August 2023. PKM activities were carried out in two sessions, first, delivery of material and practice of making charcoal briquettes starting from carbonization of sago bark, forming of charcoal briquettes and second, burning of the charcoal briquettes. The community was involved in the practice of making sago bark charcoal briquettes in order to raise their appreciations and increase their understanding of producing charcoal briquettes from sago bark.